Business potential of arctic berry wax: Organic candy industry: Value proposition and framework for business - Kippola, Vili (Oulun ammattikorkeakoulu, 2018)
This thesis project is a case study about the suitability, value proposition and possibility of market entry of the product arctic berry wax to organic candy manufacturing industry. The study was conducted as a part of an international WAX-project studying the arctic berry wax. There are four universities taking part in the research of the wax and this thesis was part of Oulu University of Applied Sciences (Oamk) WP5: Identifying the business potential of arctic berry wax. Arctic berry wax is a wax that can be gathered from the waste product of the current processing methods of the berries. Through qualitative research and analysis of documents and observations this thesis focuses on creating a value proposition for arctic berry wax regarding the candy manufacturing field. In addition to this the wax is compared to other similar products already on the market to find out the strongest existing competitors. Based on the data gathered a forecast for the potential market entry of arctic berry wax was made. The results of this thesis show that there is potential for the wax to enter the market based on the features of the wax in comparison to existing waxes on the market. However further research is required about the wax and some of the values such as arctic image of the wax don’t bring additional value for most companies in the field. For future research it is recommended to consider niche markets where the additional features of the wax could bring more value. For the business possibilities of the wax in the candy manufacturing more about possible certifications and the behavior of the wax in use needs to be studied.